Intracytoplasmic sperm injection in sturgeon species: A promising reproductive technology of selected genitors - Fatira, Effrosyni; Havelka, Miloš; Saito, Taiju; Landeira, José; Rodina, Marek; Gela, David; Pšenička, Martin (Frontiers in Veterinary Science, 2022)
Sturgeons are the most endangered species group and their wild populations continue to decrease. In this study, we apply intracytoplasmic sperm injection (ICSI), an assisted reproductive technology, for the first time in endangered and critically endangered sturgeons. Using various egg-sperm species combinations we performed different ICSI experiments with immobilized pre- or non-activated spermatozoa, single or many, fresh or cryopreserved. Then we evaluated the fertilization success as well as the paternity of the resultant embryos and larvae. Surprisingly, all experimental groups exhibited embryonic development. Normal-shaped feeding larvae produced in all egg-sperm species-combination groups after ICSI using single fresh-stripped non-activated spermatozoa, in one group after ICSI using single fresh-stripped pre-activated spermatozoa, and in one group after ICSI using multiple fresh-stripped spermatozoa. ICSI with single cryopreserved non-activated spermatozoa produced neurula stage embryos. Molecular analysis showed genome integration of both egg- and sperm-donor species in most of the ICSI transplants. Overall, ICSI technology could be used as an assisted reproduction technique for producing sturgeons to rescue valuable paternal genomes.